The Effects of Palm Oil Fuel Ash on Mechanical and Durability Properties of Sustainable Foamed Concrete - Patah, Dahlia; Dasar, Amry; Noor, Nurazuwa Md. (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
In recent years, mortar bricks or autoclaved aerated concrete (AAC), also known as foamed concrete, have been widely used as masonry wall materials. Foamed concrete, like bricks, can be produced by adding a foaming agent to achieve the desired weight and density, while meeting requirements for strength and durability. However, the search for sustainable construction materials has become imperative , including the use of waste materials to partially replace cement. The incorporation of SCM in the production of cement-based materials, such as foamed concrete, has a significant impact on reducing CO 2 emissions and promoting a sustainable environment. POFA, a secondary product derived from the palm oil industry that is typically left on the ground , poses environmental problems. Due to its good performance and pozzolanic reactions, POFA-based construction materials have great potential as alternatives to ordinary Portland cement. Unlike previous studies, this research evaluates the strength and durability of foamed concrete with variations in foam agent dosages, including finer particles of POFA (100μm) as a partial cement replacement. The study produced a total of 6 batches of foamed concrete, measuring compressive strength, porosity, water absorption, and electrical resistivity. Additionally, the research examined the correlation between compressive strength and porosity, as well as compressive strength and electrical resistivity. This study concludes that an ideal content of 10% POFA with a foaming agent-to-water ratio (fa/w) of 1/60 can achieve the best strength of foamed concrete. Furthermore, a partial cement replacement with 20% POFA could potentially increase the compressive strength to levels similar to those of normal foamed concrete (without POFA).